Bimbingan Teknis Pengawasan Pemungutan Suara dan Perhitungan Suara Pengawas TPS di Kecamatan Montong Gading pada Pemilihan Serentak Tahun 2024 - Sandy Ari Wijaya; Widya Hartati; Ratna Yuniarti; Salmi Yuniar Bahri; Nova Hari Santhi (Lembaga Pengembangan Kinerja Dosen, 2024)
The Community Service Activity (PKM) by ITSKes Muhammadiyah Selong aims to improve the ability and readiness of TPS Supervisors in carrying out supervision and understanding the rights and obligations in supervising TPS in the 2024 Simultaneous Elections (Pilkada) in Montong Gading District, East Lombok Regency. The Capacity Building Activity in the Technical Supervision Work Meeting was carried out for 1 day with a pull day system. In the first session from morning to afternoon, the capacity and abilities of TPS Supervisors were strengthened regarding the tasks and strategies for supervision before voting at TPS. After that, in the afternoon session, a technical understanding was provided regarding the procedures for supervision at TPS during the voting process until the vote counting for the 2024 Simultaneous Election based on KPU Regulation Number 7 of 2024. The last session was a discussion about the material or things that might arise when carrying out supervision at TPS. Capacity building activities in the technical work meeting for Supervision for the 2024 simultaneous elections took place at Lesehan Kebon Dowe, Lendang Belo Village, Montong Gading District on Saturday, November 23, attended by 71 participants from TPS Supervisors throughout Montong Gading District. The agenda for the capacity building activities for TPS Supervisors took place smoothly and conducively and all participants were able to understand the material presented, starting from the regulations or technical instructions for voting and vote counting as well as the supervision patterns that must be carried out by TPS Supervisors based on the provisions of laws and regulations applicable to the 2024 Simultaneous Elections.